Impact of soil amendments on nitrous oxide emissions and the associated denitrifying communities in a semi-arid environment - Fudjoe, Setor Kwami; Li, Lingling; Jiang, Yuji; Alhassan, Abdul-Rauf Malimanga; Xie, Junhong; Anwar, Sumera; Wang, Linlin; Xie, Lihua (Frontiers in Microbiology, 2022)
Denitrifying bacteria produce and utilize nitrous oxide (N2O), a potent greenhouse gas. However, there is little information on how organic fertilization treatments affect the denitrifying communities and N2O emissions in the semi-arid Loess Plateau. Here, we evaluated how the denitrifying communities responsible for potential denitrification activity (PDA) and N2O emissions. A field experiment was conducted with five fertilization treatments, including no fertilization (CK), mineral fertilizer (MF), mineral fertilizer plus commercial organic fertilizer (MOF), commercial organic fertilizer (OFP), and maize straw (MSP). Our resulted showed that soil pH, soil organic carbon (SOC), and dissolved organic nitrogen (DON) were significantly increased under MSP treatment compared to MF treatment, while nitrate nitrogen (NO3−−N) followed the opposite trend. Organic fertilization treatments (MOF, OFP, and MSP treatments) significantly increased the abundance and diversity of nirS- and nosZ-harboring denitrifiers, and modified the community structure compared to CK treatment. The identified potential keystone taxa within the denitrifying bacterial networks belonged to the distinct genera. Denitrification potentials were significantly positively correlated with the abundance of nirS-harboring denitrifiers, rather than that of nirK- and nosZ-harboring denitrifiers. Random forest modelling and structural equation modelling consistently determined that the abundance, community composition, and network module I of nirS-harboring denitrifiers may contribute significantly to PDA and N2O emissions. Collectively, our findings highlight the ecological importance of the denitrifying communities in mediating denitrification potentials and the stimulatory impact of organic fertilization treatments on nitrogen dynamics in the semi-arid Loess Plateau. Keywords: denitrifiers; functional genes; keystone taxa; nitrous oxide emissions; potential denitrification activity